Liraglutide for weight management in children and adolescents with prader-willi syndrome and obesity - DEMİRCİOĞLU, SERAP (My University, 2022)
Context Prader-Willi syndrome (PWS) is characterized by lack of appetite control and hyperphagia, leading to obesity. Pharmacological options for weight management are needed. Objective To determine whether liraglutide treatment for weight management is superior to placebo/no treatment in pediatric individuals with PWS. Methods This was a multicenter, 52-week, placebo-controlled trial with a 16-week double-blinded period. Adolescents (n = 31, aged 12-17 years; Tanner stage 2-5) and children (n = 24, aged 6-11 years; Tanner stage <2) with PWS and obesity were included. Patients were randomized 2:1 to liraglutide 3.0 mg (or maximum-tolerated dose) or placebo for 16 weeks, after which placebo was stopped. Liraglutide was continued for 52 weeks. All patients followed a structured diet and exercise program throughout the trial. The coprimary endpoints were change in body mass index (BMI) standard deviation score (SDS) from baseline to 16 and 52 weeks. Secondary endpoints included other weight-related parameters, hyperphagia, and safety. Results Change in BMI SDS from baseline to weeks 16 and 52 was not significantly different between treatments in adolescents (estimated treatment difference: -0.07 at week 16 and -0.14 at week 52) and children (-0.06 and -0.07, respectively). Changes in other weight-related parameters between treatments were not significant. At week 52, hyperphagia total and drive scores were lower in adolescents treated with liraglutide vs no treatment. The most common adverse events with liraglutide were gastrointestinal disorders. Conclusion Although the coprimary endpoints were not met, changes in hyperphagia total and drive scores in adolescents warrant further studies on liraglutide in this population.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); Endokrin ve Otonom Sistemler; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; Prader-Willi Syndrome; obesity; children; adolescents; pediatric population; BMI SDS; APPETITE; ADULTS